Optimization of nucleosome assembly from histones and model DNAs and estimation of the reconstitution efficiency - Kutuzov, M.M.; Kurgina, T.A.; Belousova, E.A.; Khodyreva, S.N.; Lavrik, O.I. (Вiopolymers and Cell, 2019)
Nucleosome core particles (NCPs) are basic units of chromatin organization; they represent the most convenient model system for the study of key DNA-dependent processes. Therefore, a robust method of nucleosome assembly is important for research. To prepare NCPs, purified histones and DNAs with sequences providing strong positioning of DNA relative to histone octamer are commonly used, and a method to control the efficacy of NCP reconstruction is required. Aim. To optimize the procedure for NCP reconstitution from purified histone octamers and different types of synthetic model DNAs and develop a new approach for express analysis of the efficacy of NCP reconstitution. Methods. Dialysis, PAAG, fluorescence measurement using the Eva-Green dye. Results. We first developed a convenient procedure for NCP assembly in a low-salt buffer with a variable DNA-histone ratio at the first stage. Once the optimal ratio was determined, NCPs could be assembled by a slow gradient dialysis. The efficacy of NCP assembly can be estimated directly in the solution using the Eva-Green dye. Conclusions. The efficacy of dye intercalation into DNA duplex was sharply reduced in the nucleosomal context. The main benefits of the proposed approach are the rapid analysis directly in the solution and possibility to use DNAs without any special tags. Нуклеосомна корова частка, НКЧ, являє собою зручну модельну систему для вивчення ключових ДНК-залежних процесів, оскільки є елементарною одиницею структури хроматину. Саме тому основним завданням представленого дослідження було створення універсального методу збірки нуклеосом. Для реконструкції НКЧ використовуються очищені гістони і ДНК-структури з певними послідовностями, що забезпечують чітке позиціонування ДНК відносно октамера гістонів. Це вимагає наявності способу контролю ефективності реконструкції НКЧ. Мета. Оптимізувати процедуру реконструкції НКЧ з очищених октамер гістонів і різних типів синтезованих модельних ДНК і запропонувати підхід для експрес-аналізу ефективності цього процесу. Методи. Діаліз, поділ в ПААГ, вимір флуоресценції з використанням барвника Eva-Green. Результати. Ми розробили зручну процедуру складання НКЧ в слабо сольовому буфері із змінним співвідношенням ДНК-гістони на першому етапі. Після визначення оптимального співвідношення реконструкція НКЧ може бути проведена за допомогою повільного градиентного діалізу. На цьому етапі ефективність процесу може бути оцінена безпосередньо в розчині з використанням барвника Eva-Green. Висновки. Було показано, що ефективність интеркаляции барвника в дуплекс ДНК в контексті нуклеосоми різко знижується. До основних переваг запропонованого підходу можна віднести швидкий аналіз суміші безпосередньо в розчині і можливість використання ДНК, що не містять будь-яких спеціальних міток. Нуклеосомная коровая частица, НКЧ, представляет собой удобную модельную систему для изучения ключевых ДНК-зависимых процессов, поскольку является элементарной единицей структуры хроматина. Именно поэтому основной задачей представленного исследования было создание универсального метода сборки нуклеосом. Для реконструкции НКЧ используются очищенные гистоны и ДНК-структуры с определенными последовательностями, обеспечивающими четкое позиционирование ДНК относительно октамера гистонов. Это требует наличия способа контроля эффективности реконструкции НКЧ. Цель. Оптимизировать процедуру реконструкции НКЧ из очищенных октамеров гистонов и различных типов синтезированных модельных ДНК и предложить подход для экспресс-анализа эффективности этого процесса. Методы. Диализ, разделение в ПААГ, измерение флуоресценции с использованием красителя Eva-Green. Результаты. Мы разработали удобную процедуру сборки НКЧ в слабо солевом буфере с изменяемым соотношением ДНК-гистоны на первом этапе. После определения оптимального соотношения реконструкция НКЧ может быть проведена с помощью медленного градиентного диализа. На этом этапе эффективность процесса может быть оценена непосредственно в растворе с использованием красителя Eva-Green. Выводы. Было показано, что эффективность интеркаляции красителя в дуплекс ДНК в контексте нуклеосомы резко снижается. К основным преимуществам предложенного подхода можно отнести быстрый анализ смеси непосредственно в растворе и возможность использования ДНК, не содержащих каких-либо специальных меток.